2001
DOI: 10.1046/j.1365-2133.2001.04220.x
|View full text |Cite
|
Sign up to set email alerts
|

The antipsoriatic drug dimethylfumarate strongly suppresses chemokine production in human keratinocytes and peripheral blood mononuclear cells

Abstract: These results show the ability of DMF to inhibit the production of chemokines that may be critically involved in the development and perpetuation of psoriatic lesions. This might explain, at least in part, the beneficial effects of treatment with fumaric acid esters in psoriasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 31 publications
7
83
1
1
Order By: Relevance
“…MIF (3) in (1,5,7,9,11) or siControl ? MIF (4) in (2,6,8,10,12). Results in vehicle (1, 2), MSK1 siRNA ?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIF (3) in (1,5,7,9,11) or siControl ? MIF (4) in (2,6,8,10,12). Results in vehicle (1, 2), MSK1 siRNA ?…”
Section: Discussionmentioning
confidence: 99%
“…Dimethylfumarate (DMF) has recently been shown to be the most effective component in the mixture of different FAEs [2][3][4]. Lately, we showed that DMF, in cultured human keratinocytes, inhibits interleukin (IL)-1b induced phosphorylation of mitogen-and stress-activated protein kinase 1 (MSK1) (Ser376), the nuclear translocation of nuclear factor (NF)-jB and the phosphorylation of NF-jB p65 (Ser276), cAMP-responsive element-binding protein (CREB) (Ser133) and activator transcription factor 1 (ATF1) which are downstream from MSK1 [5].…”
Section: Introductionmentioning
confidence: 99%
“…In human keratinocytes and peripheral blood mononuclear cells stimulated with IFN-g or LPS, dimethyl fumarate (Fig. 9) inhibits the production of chemokines that may be critically involved in the development and persistance of psoriatic lesions (426). In patients with relapsing-remitting multiple sclerosis, dimethyl fumarate reduced the formation of new inflammatory lesions in both a pilot study (392) and a multicenter, randomized, double-blind, placebo-controlled, dose-escalation, Phase IIb study (224).…”
Section: Dimethyl Fumaratementioning
confidence: 99%
“…Showing a prevailing effect on Th2-cellpromoting, so called type II, dendritic cells, these studies provide further insights on the cascades of cellular events that may follow exposure to DMF [Ghoreschi et al 2011]. Beyond its effects on T-cells and dendritic cells, DMF may also target several other immunologically active cell types, namely neutrophils, macrophages, monocytes, endothelial cells or keratinocytes [Asadullah et al 1997;Loewe et al 2002;Nibbering et al 1993;Ockenfels et al 1998;Schilling et al 2006;Sebok et al 1998;Stoof et al 2001]. …”
Section: Dimethyl Fumarate: Pharmacokinetic Datamentioning
confidence: 99%